Maʾālāt (consequences) and their uṣūlī maxims: a juristic applied study = المآلات وقواعدها الأصولية: دراسة فقهية تطبيقية - Suleiman, Hassan; Busari, Saheed Abdullahi; Adam, Musa Umar (IIUM Press, 2023)
Since the entity of Islamic Sharīʽah is full of wisdom and goodness, it is pertinent for Muslims to contemplate their future, after learning from the past experiences and the knowledge of the present. By looking ahead, and at its complexity and preparing for it with the required sciences and arts, a better society can be ensured. Hence the scholars gave importance to the jurisprudence of ma’ālāt (consequences), their uṣūlī maxims and applications in various fields of Islamic jurisprudence. This study aims to employ our Islamic knowledge of jurisprudence and its principles, maqāṣid, as well as intellectual thought in extracting the role of heritage, extrapolating the established way of Allah and studying the reality carefully, that will enable the contemplating of a better future for the Islamic nation that will lead to achieving development and prosperity. Therefore, the problem of research lies in the difficulty to use the uṣūlī maxims and rules related to the jurisprudence of the future regarding the new juristic developments in different fields of Islamic law and contemporary issues. In order to complete the research, the researchers used the inductive analytical method by extrapolating the established Sharīʽah texts to anticipate and consider the role of ma’ālāt and then analyze those texts to infer appropriate judgments based on facts. Among the major findings of the research were: first, Islam prepared man to look to the future and free him from the obstacles of superstition, pessimism, volatility and astrology, and he should not despair, and surrender; rather he should struggle for, and stand by the truth. Secondly, the maxims of maʾālāt are concerned with knowing the legitimate provisions concerning the future and the possible actions of the mukallafūn (legally responsible people) based on past experience, understanding the reality and looking ahead within the possible human ability. Thirdly, the Qur’ān was concerned with establishing natural and societal ways of Allah based on contemplating the future, the same way it paid attention to the present by linking it with the past so that the Muslim can be on a sound foundation regarding his future.